Self-Inadequacy in Daniel Caesar’s Lyrics Album Never Enough - Muhammad Sayyid Fathan Fadhlullah; Toneng Listiani; Hasbi Assiddiqi (Journal of English Language and Education, 2026)
This study examines the representation of self-inadequacy in Daniel Caesar’s Never Enough album, focusing on the songs “Ocho Rios,” “Toronto 2014,” and “Always.” While previous studies often apply Paul Ricoeur’s hermeneutics in a limited or descriptive manner, this research provides a more structured application of the hermeneutic arc as a systematic method. By focusing on textual autonomy, explanation, understanding, and the world of the text, the analysis reveals how linguistic and symbolic patterns construct feelings of inadequacy. The findings show that self-inadequacy appears in three dimensions: dependency in “Ocho Rios,” temporal stagnation in “Toronto 2014,” and emotional subordination in “Always.” Ultimately, the lyrics construct a coherent “world of the text” where the subject lacks agency and relies on external validation. This study concludes that the selected lyrics serve as a structured narrative of modern vulnerability, demonstrating the potential of song lyrics as complex interpretive texts.